1999
DOI: 10.1116/1.591059
|View full text |Cite
|
Sign up to set email alerts
|

High resolution reactive ion etching of GaN and etch-induced effects

Abstract: We have developed a process using electron beam lithography and reactive ion etching for the high resolution pattern transfer of GaN. 150 nm dots have been fabricated in GaN successfully. Photoluminescence, scanning electron microscopy, and x-ray photoelectron spectroscopy have been employed to compare the damage inflicted on the GaN surfaces after SF 6 and Ar plasma exposures. Near-band-edge luminescence analysis indicates the existence of a higher concentration of donors on the top 100 nm of the GaN surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The damage of the GaN film surfaces by the Ar-plasma etching was previously reported to consist of two defective layers in the top surface regions, one is the nitrogen-deficient surfaces limited to the top few monolayers and the other is the defect propagation region, due to the preferential etching of nitrogen. 13) However, the PL measurement results give the information of the near-surface regions rather than the top surface regions of the GaN film. 14) In our experiment, the Ar plasma exposed is considered to cause nitrogen deficiency and defects, resulting in non-radiative damage of the GaN film on the top surface region.…”
mentioning
confidence: 99%
“…The damage of the GaN film surfaces by the Ar-plasma etching was previously reported to consist of two defective layers in the top surface regions, one is the nitrogen-deficient surfaces limited to the top few monolayers and the other is the defect propagation region, due to the preferential etching of nitrogen. 13) However, the PL measurement results give the information of the near-surface regions rather than the top surface regions of the GaN film. 14) In our experiment, the Ar plasma exposed is considered to cause nitrogen deficiency and defects, resulting in non-radiative damage of the GaN film on the top surface region.…”
mentioning
confidence: 99%
“…2, the dominant transition line at 356.5 nm (3.475 eV), the I 2 line, is due to the recombination of excitons that were bound to donors [19]. Cheung et al [20] observed an additional transition in the PL spectrum of undoped GaN after Ar-reactive ion etching, which were donorbound excitons, confirming the proposed formation of shallow donors. In our PL results, however, the additional transition was not observed, indicating that the shallow donors by nitrogen vacancies are restricted to the topmost surface due to the reduced contribution to the luminescence of the surface than that of the bulk, in accordance with the R s value.…”
Section: Methodsmentioning
confidence: 74%
“…It was found that the high aspect ratio nanotip sample shows similar luminescence peak positions but less absolute intensity compared to the nanotube sample. Ruling out any redeposition of the material hypothesis, N vacancies and/or Ga interstitial defects have been reported on etched surfaces which have been found to be no longer stoichiometric because of a preferential removal of the lighter atom, i.e., nitrogen, during the etching process [36,37] and are therefore a likely candidate for the ICP-induced 3.1 eV PL. Donor-and/or acceptor-related PL signals could also come from redeposited GaN material spreading out over the facet nanostructures.…”
Section: Resultsmentioning
confidence: 97%